2021
DOI: 10.1002/cctc.202101439
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Hydrogen Evolution Using Ternary‐Metal‐Sulfide/TiO2 Heterojunction Photocatalysts

Abstract: The development of efficient and stable photocatalysts is key to achieving highly efficient photocatalytic hydrogen evolution. Compared with photocatalysts containing only one type of semiconductor, heterojunction structure photocatalyst combining two or more semiconductors show altered band alignment at the interface, which promotes the separation of photogenerated carriers and inhibits carrier recombination. Thus, this kind of photocatalysts usually exhibit higher hydrogen evolution rates. To date, binary‐me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 102 publications
0
28
0
Order By: Relevance
“…The conduction and valence band potential (E CB and E VB , respectively) of Zn x Cd 1Àx S can be calculated using the following empirical equation. [9,24,25] E CB ¼ χ-E e -1=2E g (1)…”
Section: Crystal and Band Structuresmentioning
confidence: 99%
See 4 more Smart Citations
“…The conduction and valence band potential (E CB and E VB , respectively) of Zn x Cd 1Àx S can be calculated using the following empirical equation. [9,24,25] E CB ¼ χ-E e -1=2E g (1)…”
Section: Crystal and Band Structuresmentioning
confidence: 99%
“…Cocatalyst loading is one of the most efficient strategies for improving the photoactivity of MS photocatalysts. [9] Generally, noble metals, such as Pt, Au, and their alloys, can act as electron sinks, provide sufficient active sites, and enhance charge separation, resulting in improved photoactivity for MS photocatalysts. [43,44] Shu et al reported a Pt x Fe 1Àx alloy as a cocatalyst to improve the photocatalytic HER performance of a ZnCdS photocatalyst.…”
Section: Cocatalyst Engineeringmentioning
confidence: 99%
See 3 more Smart Citations